Diet quality among adolescents has deteriorated: a panel study in Niterói, Rio de Janeiro State, Brazil, 2003-2008 - Luana Silva Monteiro; Paulo Rogerio Melo Rodrigues; Gloria Valeria da Veiga; Dirce Maria Lobo Marchioni; Rosangela Alves Pereira
This study aimed to analyze changes in the diet quality of adolescents from public schools in Niterói, Rio de Janeiro State, Brazil, over a five-year period. Data on the food consumption of adolescents (12-19 years) were obtained by means of two sets of 3-day food records in two school-based, cross-sectional studies conducted in 2003 and 2008. The Brazilian Revised Healthy Eating Index (BHEI-R) was used to estimate dietary quality. From 2003 to 2008 there was an overall decrease in the scores attributed to "total vegetables", "dark green and orange vegetables", and "meat, eggs, and legumes", but there was an increase in the score for "milk and dairy" (4.0 vs. 5.2; p < 0.01). Among female adolescents, the BHEI-R decreased (64.1 vs. 62.4; p = 0.04), as did the scores attributed to "total vegetables", "dark green and orange vegetables", "meat, eggs, and legumes", and "solid fat, alcohol, and added sugar". In contrast, among males, only the "whole grains" score decreased (0.2 vs. 0.1; p = 0.04). From 2003 to 2008, the diet quality of female public school students declined in Niterói.